2012
DOI: 10.1016/j.lfs.2012.03.022
|View full text |Cite
|
Sign up to set email alerts
|

The dual endothelin converting enzyme/neutral endopeptidase inhibitor SLV-306 (daglutril), inhibits systemic conversion of big endothelin-1 in humans

Abstract: SLV-306 leads to inhibition of both NEP and ECE in humans. Simultaneous augmentation of ANP and inhibition of ET-1 production is of potential therapeutic benefit in cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 53 publications
0
26
0
1
Order By: Relevance
“…by guest on http://circres.ahajournals.org/ Downloaded from BP and proteinuria and prevent nephrosclerosis as effectively as the ACE inhibitor captopril. 90,94 Daglutril has also been shown to be safe and well tolerated in healthy volunteers, 92,95 and biomarker measurements confirmed dual suppression of neprilysin and endothelin-converting enzyme activity in these subjects. 92 Data from a multicenter, randomized controlled trial performed in 75 patients with HF showed that daglutril reduced pulmonary and right atrial pressures without affecting systemic arterial pressure, cardiac output, or heart rate.…”
Section: Dual-acting Endothelin Converting Enzymeneprilysin Inhibitorsmentioning
confidence: 86%
See 2 more Smart Citations
“…by guest on http://circres.ahajournals.org/ Downloaded from BP and proteinuria and prevent nephrosclerosis as effectively as the ACE inhibitor captopril. 90,94 Daglutril has also been shown to be safe and well tolerated in healthy volunteers, 92,95 and biomarker measurements confirmed dual suppression of neprilysin and endothelin-converting enzyme activity in these subjects. 92 Data from a multicenter, randomized controlled trial performed in 75 patients with HF showed that daglutril reduced pulmonary and right atrial pressures without affecting systemic arterial pressure, cardiac output, or heart rate.…”
Section: Dual-acting Endothelin Converting Enzymeneprilysin Inhibitorsmentioning
confidence: 86%
“…90,94 Daglutril has also been shown to be safe and well tolerated in healthy volunteers, 92,95 and biomarker measurements confirmed dual suppression of neprilysin and endothelin-converting enzyme activity in these subjects. 92 Data from a multicenter, randomized controlled trial performed in 75 patients with HF showed that daglutril reduced pulmonary and right atrial pressures without affecting systemic arterial pressure, cardiac output, or heart rate. 89 Daglutril has also been shown in a small randomized, doubleblind, placebo-controlled crossover trial to lower BP but not to reduce albuminuria in patients with type 2 diabetes mellitus and nephropathy.…”
Section: Dual-acting Endothelin Converting Enzymeneprilysin Inhibitorsmentioning
confidence: 86%
See 1 more Smart Citation
“…Changes of hemodynamics are more difficult to cope for elderly patients, who also experience a gradual decline of GFR by 1% per year starting at age 45. Novel pharmacological approaches to block either binding or formation of ET by inhibiting ET converting enzymes (Nelissen et al, 2012;Seed et al, 2012), or by combining ERAs with drugs targeting other G protein-coupled receptors (Kowala et al, 2004;Kurtz and Klein, 2009;Mohanan et al, 2011;Murugesan et al, 2005;Neutel et al, 2008), may prove effective to block the ET pathway in disease.…”
Section: Current Perspectives For Era Therapy In Clinical Medicinementioning
confidence: 99%
“…An orally active ECE/NEP inhibitor (SLV-306 or daglutril) caused a concentration dependent attenuation of the hypertensive response to big ET-1 infusion, a parallel increase of plasma ANP levels, without changes in plasma ET-1 concentration, in healthy volunteers, suggesting that the biological active peptide can be removed from the circulation by ET B clearance receptors [99]. ECE/NEP blockade has so far revealed important protective effects on cardiac remodeling in a rat model of renovascular hypertension [100], on improvement of cardiac function and of cardiac remodeling following myocardial infarction [101].…”
Section: Atrial Natriuretic Peptide-based Therapeutic Approachesmentioning
confidence: 99%